1997
DOI: 10.1021/ac960788x
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Engineered Bacteria:  Electrochemical Sensing Systems for Antimonite and Arsenite

Abstract: A bacterial sensing system that responds selectively to antimonite and arsenite has been investigated. The bacteria used in these studies have been genetically engineered to produce the enzyme beta-galactosidase in response to these ions. This is accomplished by using a plasmid that incorporates the gene for beta-galactosidase (reporter gene) under the control of the promoter of the ars operon. This plasmid also encodes for the ArsR protein, a regulatory protein of the ars operon, which, in the absence of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
83
1
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 27 publications
1
83
1
2
Order By: Relevance
“…S5 in the supplemental material). Another undesirable property of biosensors is their elevated background signal (43,51,(53)(54)(55). The biosensors described here are characterized by very low background signals, and ␤-galactosidase activity of ϳ10 Miller units was observed in the absence of a ligand, translating into very favorable signal-tonoise ratios for arsenic measurements.…”
Section: Acidithiobacillus Ferrooxidansmentioning
confidence: 99%
“…S5 in the supplemental material). Another undesirable property of biosensors is their elevated background signal (43,51,(53)(54)(55). The biosensors described here are characterized by very low background signals, and ␤-galactosidase activity of ϳ10 Miller units was observed in the absence of a ligand, translating into very favorable signal-tonoise ratios for arsenic measurements.…”
Section: Acidithiobacillus Ferrooxidansmentioning
confidence: 99%
“…The regulatory protein of the operon, ArsR, has been shown to be a trans-acting repressor that senses environmental As(III) (32). The ArsR protein contains a very specific binding site toward As(III) and can discriminate effectively against phosphate, sulfate, cobalt, and cadmium (28). ArsR has a strikingly high affinity, as even 10 Ϫ15 M As(III) could induce the ars promoter (22).…”
mentioning
confidence: 99%
“…crtIBS exhibited Ͼ500-fold-lower sensitivity to arsenate. Despite the fact that we used Pars and arsR from E. coli, the sensitivity of crtIBS to arsenate was significantly lower than the sensitivities of E. coli-based luciferase biosensors (23,26). It has been reported that arsenate is reduced to arsenite by the reductase in E. coli, and arsenite induces light emission.…”
Section: Discussionmentioning
confidence: 91%
“…Such systems indicate the presence of a target molecule by expressing a reporter protein, such as green fluorescent protein, luciferase, or ␤-galactosidase. Several arsenite biosensors harboring a reporter gene fused with the operator-promoter region of the ars operon have been constructed (4,20,23,26,28,29). The ars operon of Escherichia coli contains two regulatory genes (arsR and arsD) and three structural genes (arsA, arsB, and arsC) and has been shown to confer resistance to arsenite in its host (5,22).…”
mentioning
confidence: 99%